OTORITAS FATWA MUI PROVINSI SULAWESI SELATAN NOMOR 1 TAHUN 2021 TENTANG EKSPOLITASI KEGIATAN PENGEMIS DI JALANAN RUANG PUBLIK PERSPEKTIF SIYASAH SYARIYYAH - Ridwan, Mir'atul Mar'ah; Kurniati, Kurniati; Syatar, Abdul; Mustafa, Zulhas'ari (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to describe the views of the Mui Fatwa Authority of South Sulawesi Province Number 1 of 2021 concerning the Exploitation and Activities of Beggars on the Streets to Public Spaces from the Siyasah Syariyyah Perspective. In answering this problem, the author uses a normative syar`i approach and an empirical juridical approach. The method of data collection is done by way of interviews, observation, documentation, and literature study. The results of the research show that MUI Fatwa Number 1 of 2021 provides guidelines for Muslims regarding procedures for providing assistance to beggars that are more useful and encourage them to get out of the poverty cycle independently and with justice. Furthermore, the exploitation of street begging activities involving violations of laws is not recommended in Islam. From the perspective of Siyasah Syariyyah, the MUI fatwa regarding the prohibition of providing assistance to beggars on the streets can be seen from legal and political aspects. Basically, we as citizens who are good and obedient to religious rules should carry out the fatwa rules that have been issued by the Indonesian Ulema Council and should socialize more to the whole community so that the fatwas that have been issued are better understood and implemented in accordance with the regulations that have been made.